Neutral Current in Reduced Minimal 3-3-1 Model - Huyen, Vu Thi Ngoc; Long, Hoang Ngoc; Lam, Tran Thanh; Phong, Vo Quoc (Communications in Physics, 2014)
This work is devoted for gauge boson sector of the recentlyproposed model based on \(SU(3)_C\otimes SU(3)_L\otimes U(1)_X\) group with minimal content of leptons andHiggses. The limits on the masses of the bilepton gauge bosons andon the mixing angle among the neutral ones are deduced. Using theFritzsch anzats on quark mixing, we show that the third family ofquarks should be different from the first two. We obtain a lowerbound on mass of the new heavy neutral gauge boson as 4.032 TeV.Using data on branching decay rates of the \(Z\) boson, we can fix the limit to the \(Z\) and $Z^′$ mixing angle\(φ\) as \(-0.001\leφ\le 0.0003\).